Rotary Flexible Joint Control Using Adaptive Fuzzy Sliding Mode Scheme. (5th September 2022) - Aljohani, Abdulah Jeza; Mehedi, Ibrahim M.; Bilal, Muhammad; Mahmoud, Mohamed; Meem, Rahtul Jannat; Iskanderani, Ahmed I.M.; Alam, Md Mottahir; Alasmary, Waleed
Abstract : An adaptive fuzzy sliding control (AFSMC) approach is adopted in this paper to address the problem of angular position control and vibration suppression of rotary flexible joint systems. AFSMC consists of fuzzy-based singleton control action and switching control law. By adjusting fuzzy parameters with the self-learning ability to discard system nonlinearities and uncertainties, singleton control based on fuzzy approximation theory can estimate the perfect control law of feedback linearization. To enhance robustness, an additional switching control law is incorporated to reduce the approximation error between the derived singleton control action and the perfect control law of feedback linearization. AFSMC's closed-loop stability will be demonstrated via sliding surface and Lyapunov function analysis of error function. In order to demonstrate the effectiveness of the AFSMC in tracking performance as well as its ability to respond to model uncertainties and external perturbations, simulations are carried out using Simulink and Matlab in order to demonstrate how well it adapts to these situations. Based on these results, it can be concluded that the AFSMC performs satisfactorily in terms of tracking.